Penerapan Model Pembelajaran Inkuiri Terbimbing Terhadap Motivasi Belajar Fisika Pada Materi Fluida Di Kelas XI SMAN 12 Makassar - fahrunnisa fahrunnisa; Andi Nurfadilah (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
this research is to evaluate the application of the guided inquiry learning model to the physics learning motivation of class XI students at SMAN 12 Makassar. Method applied was Quasi Experimental with a two group pretest-posttest design, one group acted as the experimental group and the other group as the control group. Population was all class XI students of SMA Negeri 12 Makassar using a purposive sampling technique with class The instrument used was a student physics learning motivation questionnaire in the form of multiple choice with 24 questions. The research showed that the average pretest score in the experimental class was 88.75, while in the control class it was 87.21. The average posttest score in the experimental class increased to 104.16, while the average posttest score in the control class was lower, namely 92.90. Data analysis using the N-Gain test, an increase of 49.31 was obtained in the experimental class with medium criteria and the N-Gain in the control class experienced an increase of 17.35 which was categorized as low. So, it can be concluded that the application of the guided inquiry learning model can increase the physics learning motivation of class XI students at SMA Negeri 12 Makassar.